Raloxifene decreases cell viability and migratory potential in prostate cancer cells (LNCaP) with GPR30/GPER1 involvement - Salata, Giovanna Cassone [UNESP]; Pinho, Cristiane Figueiredo [UNESP]; de Freitas, André T. A. G. [UNESP]; Aquino, Ariana Musa [UNESP]; Justulin, Luis Antonio [UNESP]; Mendes, Leonardo Oliveira; Gonçalves, Bianca F. [UNESP]; Delella, Flávia Karina [UNESP]; Scarano, Wellerson Rodrigo [UNESP] (Oxford University Press (OUP), 2019)
Objectives: This study evaluated raloxifene (ral) effects on LNCaP prostate tumour cells modulating the activity of GPER1/GPR30 receptors. Methods: LNCaP cells were submitted for 40/120 min and 12 h to the following treatments: C: RPMI + DMSO; R: RPMI + Ral; G: RPMI + Ral + G15 (GPER1 antagonist). Trypan blue staining measured cell viability. Migratory potential (12 h) was measured by transwell migration test in translucent inserts, which were then stained with DAPI and analysed under a fluorescence microscope for quantification. Cells from 40- and 120-min treatments were subjected to protein extraction to the study of AKT, pAKT, ERK, pERK, ERβ and SIRT1. Key findings: There is a reduction in cellular viability in R compared to C at all evaluated times, and an increased cell viability in G when compared to R; cell viability was similar in C and G in all times studied. The migration assay demonstrated a significant decrease in migration potential of tumour cells in R compared to C and G. Ral treatment reduced pERK expression and increased pAKT in the treated groups after 40 min, pointing out to an antiproliferative and apoptotic effect in the GPER1-controlled rapid-effect pathways. Conclusions: Raloxifene was able to modulate GPER1 in LNCaP prostate tumour cells, decreasing cell viability and their migratory potential.
Keywords: cell viability; GPER1/GPR30 receptor; LNCaP cells; migratory potential; raloxifene